Pragmatism and Nationalism: Industrialization Policy in Indonesia and Nigeria - Ahmad Helmy Fuady (Economics and Finance in Indonesia, 2015)
This paper examines industrialization policy in two oil giant economies, Indonesia and Nigeria. What are the key features of continued economic divergence in these two countries since the 1980s? It shows that Indonesia’s policy-makers adopted a series of liberalization measures and switched to an export-oriented strategy to develop manufacturing industries from the mid-1980s, while Nigeria’s policy-makers was reluctant to do so. This paper also seeks to understand the rationale behind the different policy choices. This paper argues that policy-makers’ experience and educational background are possible explanation to the different industrialization policies in these two countries.